Mobile application for metabolic syndrome screening in climacteric women: Applied methodological study (Revista Contexto & Saúde, 2025)
The objective of this work was to present the development of an application to track metabolic syndrome in climacteric women. As for the methodology, it was an applied research developed from a study that evaluated the ability of anthropometric measures to discriminate metabolic syndrome in climacteric women. A database was created with extraction of logistic regression models and the application for smartphones was developed. Flutter, software development kit, created by Google, was used. As a result, the application called ClimatMed was developed, which is available for free in the Play Store and can be installed on smartphones with Android system. It is composed of home screen, screens for the definition of the climacteric period and adjusted variables. Measures for the calculation of the indices can be entered and the application provides the probability of development of metabolic syndrome. It is concluded that the inclusion of a computer technology in the assistance to climacteric women predisposed to develop metabolic syndrome brings positive repercussions, because it allows savings in a simple and accessible way. In addition, the identification of this population predisposed to develop metabolic syndrome helps in preventing chronic cardiovascular diseases.
Keywords: Climacteric; Metabolic Syndrome; Primary Health Care; Anthropometry